Seasonal variability of nektonic community structure and phylogenetic diversity in Weizhou Island, the Beibu Gulf - Xu, Lei; Du, Feiyan; Tang, Quehui; Wang, Lianggen; Ning, Jiajia; Huang, Delian; Li, Yafang; Liu, Shuangshuang; Wang, Xuehui (Frontiers in Marine Science, 2023)
The favorable natural conditions and variety of habitats in the Beibu Gulf provide a basis for harboring a high diversity of marine organisms. Sustainable coastal ecosystem management can be benefited from a comprehensive assessment of species diversity. In this study, we analyzed the seasonal changes in nektonic phylogenetic and community structures in the waters of Weizhou Island in the northern Beibu Gulf. The results showed that both the nektonic phylogenetic diversity and community structure in the northern Beibu Gulf exhibited strong seasonal differences between spring and autumn. The catch density was 291.9 kg per km2 in spring and 1081.1 kg per km2 in autumn. Phylogenetic diversity of nektonic communities obviously increased from spring to autumn, while phylogenetic patterns changed from clustering to overdispersion. The seasonal patterns of nektonic communities were mainly related to the different fishing intensities in spring and autumn. Summer fishing intensity in the Beibu Gulf was effectively controlled by a mid-summer fishing moratorium, during which nektonic diversity and fish stocks rapidly recovered from the larval pool. Our study revealed that fishing intensity had a greater impact on nektonic communities at smaller spatial scales, and even exceeded the effects of environmental factors.